The Impact of the War and Migration Crises on the Functioning of Children and Refugee Families From Ukraine in Poland. Research Report - Anna Linka (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: Identification of challenges and preliminary recommendations for working with refugee families in Poland. THE RESEARCH PROBLEM AND METHODS: The study aims to identify challenges shared by previous and Ukrainian refugee families in Poland and is a part of ongoing qualitative, study where ethnopedagogical method, narrative interviews, critical case sampling and key/purposive case sampling were used. In further studies (triangulation) sensitive cases sample will be used.  THE PROCESS OF ARGUMENTATION: The aim of the research is to diagnose challenges common to refugee families and, in further research, specific to Ukrainian families in Poland. RESEARCH RESULTS: Problems common to both groups of refugee families include: experiencing the disaster curve, acculturation stress, and specific experiences of migrating children and families. CONCLUSIONS, RECOMMENDATIONS AND APPLICABLE VALUE OF RESEARCH: The recommendations suggest selected ways of solving the problems of refugee families by professionals working with them.